2021
DOI: 10.1016/j.radcr.2021.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer presenting with pulmonary cannonball lesions

Abstract: Cannonball lesions are numerous, well-circumscribed, round pulmonary lesions and may be identified on plain radiograph or advanced imaging. This morphology can be associated with infectious causes, rheumatologic disease and metastatic disease. Classically, when cannonball lesions are associated with metastatic disease, they are seen in renal cell carcinoma and choriocarcinoma. We report a case of a 62-year-old Middle Eastern male who presented with shortness of breath, chest pain and fatigue and was found to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Immunotherapeutic targets like Ipilimumab and nivolumab will conduct the program cell death of the ligand-1 (PD-L1), program Although X-ray findings mimicking "Cannonball" lung lesions typically denote malignancy metastases [1], this does not necessarily mean that way. Table 2 denotes various diagnoses and each lung imaging characteristic [1,17]. A study reported a "Cannonball" appearance after spontaneous rib fracture [18], while pulmonary cavernous hemangiomas and benign satellite tumors also manifested in lung lesions mimicking Cannonball [5,19].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapeutic targets like Ipilimumab and nivolumab will conduct the program cell death of the ligand-1 (PD-L1), program Although X-ray findings mimicking "Cannonball" lung lesions typically denote malignancy metastases [1], this does not necessarily mean that way. Table 2 denotes various diagnoses and each lung imaging characteristic [1,17]. A study reported a "Cannonball" appearance after spontaneous rib fracture [18], while pulmonary cavernous hemangiomas and benign satellite tumors also manifested in lung lesions mimicking Cannonball [5,19].…”
Section: Discussionmentioning
confidence: 99%